An Immanent Critique of Decolonization Discourse - Dhillon, Sunny (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
This piece argues that contemporary neoliberal UK universities are necessarily unable to enact decolonization owing to a contradiction between their business needs and a genuine commitment to the decolonial, which involves the complete dismantling of existing colonial discourse. Using the process of immanent critique modelled by Adorno, it is argued that the neoliberal university presents inherent contradictions that demand measurable knowledge, preordained by existing colonial epistemological boundaries. A scholar engaged in immanent critique may facilitate the potential for decolonial practices within, and against, the university apparatus.